THU0013 IL-17A AND IL-17F ARE SECRETED BY ENTHESIS T CELLS AND SYNERGIZE WITH TNF TO INDUCE CCL20 FROM ENTHESEAL STROMAL CELLS. (June 2019) - Bridgewood, Charlie; Russell, Tobias; Watad, Abdulla; Rowe, Hannah; Zhou, Qiao; Khan, Almas; Loughenbury, Peter; Rao, Abhay S; Millner, Peter; Dunsmuir, Robert; Cuthbert, Richard; Mcgonagle, Dennis
Abstract : Background: Enthesitis or inflammation of tendon/ligament anchorage points is the cardinal lesion in spondyloarthritis (SpA)[1]. Human SpA is thought to be driven by IL-17 producing T-cells and can be successfully therapeutically targeted with anti-IL-17A and more recently anti-IL-17F[2]. The CCR6-CCL20 axis is thought to be crucial to tissue recruitment of IL-17 producing T-cells into tissues, however it is presently unknown if CCR6+ T-cells reside at the healthy human enthesis[3]. Moreover, the ability of IL-17 to drive CCL20 production and hence to promote further T-cell migration to the enthesis has not been tested. Objectives: To determine if enthesis T cells secrete IL-17A and IL-17F. To determine if CCR6+ T-cells reside at the normal human enthesis. To study the effect of both IL-17A and IL-17F on CCL20 induction from entheseal stromal cells. Methods: Normal spinous process enthesis was obtained from patients undergoing spinal decompression or surgery for scoliosis correction. Following enzymatic digestion, CD4+ and CD8+ T cells were stimulated with anti CD3/CD28 and IL-17A and IL-17F measured by intracellular FACS. Stromal cells were isolated from both the peri-entheseal bone (PEB) and enthesis soft tissue (ST). Stromal cells were stimulated with combinations of IL-17A or IL-17F and TNF and subsequently CCL20 was measured by ELISA. Normal PEB and ST were also analysed for the presence CCR6+ T-cells by multiparameter FACS including CD4+ and CD8 Results: Entheseal CD4+ cells secreted IL-17A and IL-17F following stimulation. When used as single agents IL-17A, IL-17F and TNF were able to induce minimal CCL20 from entheseal stromal cells, but great synergy was reported between IL-17A/TNF and IL-17F/TNF. No synergy was reported for IL-17A/IL-17F. CCR6+ CD4+ and CD8+ cells were also confirmed in the enthesis. Conclusion: Resident CD4+ T cells at the enthesis secrete IL-17A and IL-17F following stimulation. The normal human enthesis contains CCR6+ T cell populations, suggesting a CCR6/CCL20 axis is important to entheseal homeostasis. IL-17A/F dramatically synergize with TNF to induce CCL20 from enthesis stromal cells, which would be well placed to mediate further migration of IL-17 producing lymphocytes to entheseal tissues. References: [1] Bridgewood, C., et al., Spondyloarthritis: new insights into clinical aspects, translational immunology and therapeutics. Current opinion in rheumatology, 2018. 30(5): p. 526-532. [2] Hall, A.O.H., J.E. Towne, and S.E. Plevy, Get the IL-17F outta here! Nature immunology, 2018: p. 1. [3] Singh, S.P., et al., Human T cells that are able to produce IL-17 express the chemokine receptor CCR6. The Journal of Immunology, 2008. 180(1): p. 214-221. Disclosure of Interests: Charlie Bridgewood: None declared, Tobias Russell Grant/research support from: PhD Project is funded by Novartis., Abdulla Watad: None declared, Hannah Rowe: None declared, Qiao Zhou: None declared, Almas Khan: None declared, Peter Loughenbury: None declared, Abhay S Rao: None declared, Peter Millner: None declared, Robert Dunsmuir: None declared, Richard Cuthbert: None declared, Dennis McGonagle Consultant for: Lilly, Novartis UCB, Speakers bureau: Lilly, Novartis UCB